The hybrid Filipino in love teams locating the love team in the third space - Flores, Mica Patricia V.; Tolentino-Canlas, Daphne Tatiana (Quezon City College of Mass Communication, University of the Philippines Diliman, 2018)
Abstract
Love teams are abundant sites of cultural analysis. They are manufactured marketing tools with variegated symbols subject to multiple interpretations. In this study, these tools will be viewed under the lens of the postcolonial theory, particularly Homi K. Bhabha's "Third Space" which is a contact zone of two cultures or an encounter of two individuals that create a new cultural form or social practice. It is best articulated through Bhabha's concepts of hybridity, mimicry, and ambivalence. This research aims to examine the roles portrayed by popular love teams Kathryn Bernardo and Daniel Padilla, Alden Richards and Maine Mendoza, and James Reid and Nadine Lustre in order to analyze how the love teams act as a Third Space in mainstream television. The study uses qualitative content analysis in examining the characters from selected episodes of Got to Believe, Kalyeserye, and On the Wings of Love. Through the Third Space, love teams portray a hybrid representation which suggests the ambivalence of Filipinoness. It is capable of producing new cultural forms as with the case of AlDub and JaDine and it rearticulates love as an equalizer that helps create a particular space for individuals without the restrictions of position.

Keywords: love team, hybridity, postcolonial, identity, Filipino.
Abstrak
Ang mga love team ay mga kultural na produkto na malimit mapasailalim sa maraming pagpapakahulugan dulot ng iba't ibang simbolong nilalaman nito. Sa pagsasaliksik na ito, ang mga love teams ay sinuri gamit ang lente ng teoryang postkolonyal. Sa partikular, ginamit dito ang modelong "Third Space" ni Homi K. Bhabha, kung saan ang pagtatagpo ng dalawang magkaibang kultura, ideolohiya, sistema, o indibidwal ay maaaring lumikha ng panibagong kultural na anyo o gawi. Ang modelong ito ay naipapaliwanag gamit ang mga konsepto ni Bhabha na paghahalo ng kultura o hybridity, panggagagad o mimicry, at pagtitigalawa o ambivalence. Nais ng pag-aaral na itong suriin ang mga karakter na ginampanan ng mga popular na love team na sina Kathryn Bernardo and Daniel Padilla, Alden Richards and Maine Mendoza, at James Reid and Nadine Lustre upang malaman kung paano sila umasal bilang isang Third Space sa telebisyon. Ginamit sa pagsasaliksik na ito ang qualitative content analysis sa pagsisiyasat sa mga karakter mula sa mga piling episode ng Got to Believe, Kalyeserye, and On the Wings of Love. Gamit ang Third Space, ang mga love team ay natuklasang naglalarawan ng hybrid na representasyon, na may kakayahang magbunga ng panibagong kultural na anyo, at may kakayahang magbigay ng panibagong kahulugan sa mga konsepto.

Keywords: love team, hybridity, postcolonial, identity, Filipino.
Vita.
Keywords: Cultural fusion .; Postcolonialism -- Race identity